Extrapulmonary lymphomatoid granulomatosis presenting as Pancoast's syndrome. Issue 792 (October 1991) - Dolan, G.; Smith, J.; Reilly, J. T.
Abstract : We report the case of a 55 year old man who presented as Pancoast's syndrome associated with a left sided Horner's syndrome, a mass in the left supraclavicular fossa and marked weakness with wasting of the left arm consistent with a left sided brachial plexus lesion. Biopsy revealed the typical features of lymphomatoid granulomatosis. Neurological involvement is a rare presenting manifestation of this uncommon disease. Lymphomatoid granulomatosis should be considered as a rare but potentially treatable cause of Pancoast's syndrome.